Suitability of coir fibers as pulp and paper - Main, Nor Mazlana; A. Talib, Rosnita; Ibrahim, Rushdan; Abdul Rahman, Russly; Mohamed, Ainun Zuriyati (Elsevier (ScienceDirect), 2014)
This study was to investigate the suitability of coir fibers as an alternative material in making pulp and paper. Maceration process was used to characterize the fiber. Soda-AQ pulping with various combinations of active alkali (18-22%) and cooking time (90-150 minutes) at fixed temperature was done. Physical properties evaluated were density, brightness, opacity, scattering coefficient, tear, burst and tensile index. As concentration of active alkali and cooking time increased, the physical properties values also increased, except for the opacity and scattering coefficient. The optimum condition for producing the strongest paper is using 22% active alkali in 120 minutes.